1987
DOI: 10.1002/jhet.5570240357
|View full text |Cite
|
Sign up to set email alerts
|

A simple regioselective synthesis of pyrimido[1,2‐a]benzimidazoles

Abstract: 2‐Aminobenzimidazoles were reacted with enaminones in acetic acid to give pyrimido[1,2‐a]benzimidazoles. With a substituted enaminone only one regioisomer was obtained. Structural assignments based on nmr and uv spectroscopy are presented. Possible pathways leading to the products are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…1,7 However, only moderate yields of the desired products 2a-e were obtained. Consequently we have modified this synthetic approach and condensed these ketones with DMFDMA in absence of solvent.…”
Section: Resultsmentioning
confidence: 99%
“…1,7 However, only moderate yields of the desired products 2a-e were obtained. Consequently we have modified this synthetic approach and condensed these ketones with DMFDMA in absence of solvent.…”
Section: Resultsmentioning
confidence: 99%
“…While reproduction of the first reaction step (i.e. 3 → 4) took place in excellent yield, 5 we had to encounter some difficulties with the subsequent two reaction steps: rather low yields and intensive decompositions were experienced. As a result of an ongoing search for suitable reaction conditions for the desired synthesis, however, we have found that by the help of two modifications both transformations can be carried out in satisfactory and well reproducible yields.…”
Section: Resultsmentioning
confidence: 99%
“…The enaminone derivatives (8a-d) were prepared via condensation of the appropriate aryl or heteroaryl methyl ketone with dimethylformamide dimethylacetal (DMFDMA) in xylene following procedures applied in literatures [15][16][17][18][19][20][21] . Cyclocondensation of the appropriate enaminone (8a-d) with 4-hydrazinylbenzenesulfonamide hydrochloride (9a) 22 , methanesulfonylphenylhydrazine hydrochloride (9b) 23,24 or 4-hydrazinobenzoic acid (9c) 25 in aqueous ethanol afforded the respective 1,5-diarylpyrazoles (10a-l) in good yields (56-88%) (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…Silica gel column chromatography was performed using Merck silica gel 60 ASTM (70-230 mesh). Compounds 8a-d [15][16][17][18][19][20][21] , 9a-c [22][23][24][25] were prepared according to the reported procedures.…”
Section: Chemistrymentioning
confidence: 99%